Glucocorticoid-Mediated Developmental Programming of Vertebrate Stress Responsivity - Gans, Ian M.; Coffman, James A. (Frontiers in Physiology, 2021)
Glucocorticoids, vertebrate steroid hormones produced by cells of the adrenal cortex or interrenal tissue, function dynamically to maintain homeostasis under constantly changing and occasionally stressful environmental conditions. They do so by binding and thereby activating nuclear receptor transcription factors, the Glucocorticoid and Mineralocorticoid Receptors (MR and GR, respectively). The GR, by virtue of its lower affinity for endogenous glucocorticoids (cortisol or corticosterone), is primarily responsible for transducing the dynamic signals conveyed by circadian and ultradian glucocorticoid oscillations as well as transient pulses produced in response to acute stress. These dynamics are important determinants of stress responsivity, and at the systemic level are produced by feedforward and feedback signaling along the hypothalamus-pituitary-adrenal/interrenal axis. Within receiving cells, GR signaling dynamics are controlled by the GR target gene and negative feedback regulator fkpb5. Chronic stress can alter signaling dynamics via imperfect physiological adaptation that changes systemic and/or cellular set points, resulting in chronically elevated cortisol levels and increased allostatic load, which undermines health and promotes development of disease. When this occurs during early development it can “program” the responsivity of the stress system, with persistent effects on allostatic load and disease susceptibility. An important question concerns the glucocorticoid-responsive gene regulatory network that contributes to such programming. Recent studies show that klf9, a ubiquitously expressed GR target gene that encodes a Krüppel-like transcription factor important for metabolic plasticity and neuronal differentiation, is a feedforward regulator of GR signaling impacting cellular glucocorticoid responsivity, suggesting that it may be a critical node in that regulatory network.